Content Marketing, Influencer Marketing, and Online Customer Reviews as Determinants of TikTok Shop Customer Satisfaction - Totti Terichy; Melfrianti Romauli Purba (MAR-Ekonomi: Jurnal Manajemen, Akuntansi Dan Rumpun Ilmu Ekonomi, 2026)
This study analyzes the effects of content marketing, influencer marketing, and online customer reviews on TikTok Shop customer satisfaction among students of the Faculty of Economics, Universitas Prima Indonesia, Medan. The study employed a quantitative approach with an associative research design. Primary data were collected through questionnaires distributed to active TikTok Shop users, and 321 respondents were selected from a population of 1,622 students using purposive sampling and the Slovin formula with a 5% margin of error. The data were analyzed using SPSS 25 through validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination. The findings reveal that content marketing, influencer marketing, and online customer reviews each have a positive and significant effect on customer satisfaction. Among the three variables, influencer marketing was found to be the most dominant factor affecting customer satisfaction. Simultaneously, the three independent variables also have a significant joint effect on TikTok Shop customer satisfaction. These findings indicate that customer satisfaction in digital commerce is shaped by the combined influence of relevant and reliable content, credible influencer promotion, and authentic customer reviews. This study contributes to the digital marketing literature by emphasizing the importance of integrated marketing strategies in enhancing customer satisfaction on shoppertainment-based e-commerce platforms such as TikTok Shop.